2002
DOI: 10.1017/s1357729800052899
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation of the first dominant follicle arising after day 21post partumin suckling beef cows

Abstract: The effects of body condition score (BCS) of 2·0 or 3·0 units at calving (low v. moderate), post-partum energy intake at 0·6 or 1·0 MJ metabolizable energy (ME) per day per kg M0·75 (low v. high) and unrestricted or restricted (once daily) suckling on the ability of cows to ovulate were studied in a 2 ✕ 2 ✕ 2 factorial design with each treatment replicated eight times. Calf isolation and restricted suckling were imposed shortly after selection of the first dominant follicle (DF) to emerge after day 21 post par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 43 publications
3
32
0
6
Order By: Relevance
“…In the study of Stagg et al, (1998) a total of 43%, 65% and 90% of cows had ovulated by 80 days postpartum for cows with ad libitum calf access, suckled once daily suckling with calves Diskin and Kenny penned adjacent to their dams and suckled once daily suckling with calves isolated from their dams, respectively. Interestingly, in both of the studies of Stagg et al (1998) and Sinclair et al (2002) a small proportion (circa 15%) of cows failed to respond to the removal of the suckling/maternal calf bond and showed no increase in LH pulse frequency and no evidence of an increase in the circulating concentrations of oestradiol. These 'non-responders' typically had prolonged postpartum anoestrous intervals and could be described as being in 'deep anovulatory anoestrus' (Sinclair et al, 2002).…”
Section: Suckling-maternal Bondmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Stagg et al, (1998) a total of 43%, 65% and 90% of cows had ovulated by 80 days postpartum for cows with ad libitum calf access, suckled once daily suckling with calves Diskin and Kenny penned adjacent to their dams and suckled once daily suckling with calves isolated from their dams, respectively. Interestingly, in both of the studies of Stagg et al (1998) and Sinclair et al (2002) a small proportion (circa 15%) of cows failed to respond to the removal of the suckling/maternal calf bond and showed no increase in LH pulse frequency and no evidence of an increase in the circulating concentrations of oestradiol. These 'non-responders' typically had prolonged postpartum anoestrous intervals and could be described as being in 'deep anovulatory anoestrus' (Sinclair et al, 2002).…”
Section: Suckling-maternal Bondmentioning
confidence: 99%
“…Interestingly, in both of the studies of Stagg et al (1998) and Sinclair et al (2002) a small proportion (circa 15%) of cows failed to respond to the removal of the suckling/maternal calf bond and showed no increase in LH pulse frequency and no evidence of an increase in the circulating concentrations of oestradiol. These 'non-responders' typically had prolonged postpartum anoestrous intervals and could be described as being in 'deep anovulatory anoestrus' (Sinclair et al, 2002). In the latter study there was evidence of an association between low circulating concentrations of insulin, during the early postpartum period, and the failure to record an ovulatory response to calf separation/isolation thus emphasising the importance of nutrition as a regulator of PPI.…”
Section: Suckling-maternal Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the small proportion of cows that fail to respond to the removal of the suckling/maternal calf bond show no increase in LH pulse frequency, and no evidence of an increase in the circulating concentrations of oestradiol. These non-responders typically had prolonged postpartum anoestrous intervals and could be described as being in "deep anovulatory anoestrus" (Sinclair et al, 2002).…”
Section: Anovulatory Anoestrusmentioning
confidence: 99%
“…Plasma insulin concentrations are influenced by both BCS and level of nutrition (Vizcarra et al, 1998), and may serve as a more sensitive indicator of nutritional status than BCS. In a transnational study, Sinclair et al (2002) showed that postpartum anoestrous beef cows with low (<5 mIU/l) plasma concentrations of insulin were unable to ovulate a dominant follicle in response to restricted suckling, unlike cows with higher (>5 mIU/l) plasma concentrations of insulin, notwithstanding an increase in LH pulse frequency. The results of that study are consistent with those of Gong et al (2001Gong et al ( , 2002 who showed that dairy cows fed a diet, which increased circulating concentrations of insulin during the first 50 days postpartum had shorter postpartum anoestrous intervals, independent of any effects on LH or FSH and without affecting milk yield or energy balance.…”
Section: Anovulatory Anoestrusmentioning
confidence: 99%